A 2007 Social Accounting Matrix (SAM) Database for Zambia - Zambia Institute for Policy Analysis and Research; International Food Policy Research Institute (International Food Policy Research Institute, 2014)
This data study includes Zambian Social Accounting Matrix (SAM) for the year 2007. The national SAM is built using new input-output use tables, national accounts, government budgets, and balance of payments, and so provides a detailed representation of the Zambian Economy. It separates 44 activities and commodities; labor is dis-aggregated by education level; and households by rural and urban per capita expenditure quintiles. Information on labor is drawn from the 2006 Living Conditions Monitoring Survey. Finally, the SAM identifies government, investment and foreign accounts. It is therefore an ideal database for conducting economy wide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.